(3TQM GdHNGQjs - (3TeS GdOjf eMeO GdSajQj GdMdHjs; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s ((3fGUQ Hf YjSi s)
(3ChdgG (B:s
(3GdeLdS GdChd aj JQLeI GdoHNGQi QVi Gddg Yfg hfaYfG Hg haj PcQ TF ef aVGFdg aEfg cGf ef CcGHQ GdYdeGA hGdChdjGA s
(3BNQgG (B:s
(3aSGHbJg aSHbJg aScJ Yfj MJi EPG MedJ GddMe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs